Perbandingan Hukum Pidana Penelantaran Anak di Indonesia dan Belanda - Nahdiya Sabrina; Aris Hardinanto (Fakultas Hukum Universitas Islam Indonesia, 2024)
Child neglect in Indonesia is a type of child abuse with quite high cases. The problem raised in this research is the absence of clear limitations regarding child neglect, as well as the absence of specific regulations related to sanctions for child neglect in terms of obligations for the education of children of compulsory school age. Law Number 20 of 2003 concerning the National Education System. The formulation of the problem in this research is how child neglect is regulated in Indonesian criminal law and Dutch criminal law, as well as how appropriate child neglect is regulated in Indonesian criminal law. The research method used in this research is the normative legal research method, through a statutory approach and a comparative approach. Analysis of legal materials is carried out using qualitative descriptive methods. The comparison of criminal law in terms of child neglect in Indonesia and in the Netherlands is that the Netherlands adheres to a strict codification system, however in the Netherlands, there are still special regulations regarding guarantees for children in terms of getting an education through registration at a school as well as criminal sanctions for those in charge of the child if these obligations were not carried out. Meanwhile, in Indonesia Law No. 20 of 2003 concerning the National Education System does not contain specific sanctions regarding not providing basic education to children of compulsory school age. Law No. 23 of 2002 and Law No. 35 of 2014 concerning child protection also doesn't specifically regulate sanctions for parties who do not provide basic education for children of compulsory school age, and there are no clear limitations to the term child neglect. -